Shock in the First 24 h of Intensive Care Unit Stay. Issue 5 (May 2015) - See, Kay Choong; Mukhopadhyay, Amartya; Lau, Samuel Chuan-Xian; Tan, Sandra Ming-Yien; Lim, Tow Keang; Phua, Jason
<x xml:space="preserve">Abstract</x> ABSTRACT Precision in fluid management for shock could lead to better clinical outcomes. We evaluated the association of protocol-based fluid management with intensive care unit (ICU) and hospital mortality. We performed an observational study of mechanically ventilated patients admitted directly from our emergency department to the ICU from August 2011 to December 2013, who had circulatory shock in the first 24 h of ICU stay (systolic blood pressure <90 mmHg at ICU admission or lactate >4 mmol/L). Patients with onset of shock beyond 24 h of ICU stay were excluded. Protocol-based fluid management required close physician-nurse cooperation and computerized documentation, checking for fluid response (≥10% arterial pulse pressure or stroke volume increase after two consecutive 250-mL crystalloid boluses), and fluid loading with repeated 500-mL boluses until fluid response became negative. Six hundred twelve mechanically ventilated patients with shock (mean [±SD] age, 63.0 years [16.5]; 252 or 41.2% females; mean Acute Physiology and Chronic Health Evaluation II score, 30.2 [8.8]) were studied. The fluid management protocol was used 455 times for 242 patients (39.5% of 612 patients) within the first 24 h of ICU stay, with 244 (53.6% of 455) positive responses. Adjusted for age, sex, Acute Physiology and Chronic Health Evaluation II score, comorbidity, and admission year, protocol use was associated with reduced ICU mortality (odds ratio, 0.60; 95% confidence interval, 0.39–0.94; P = 0.025) but not hospital mortality (odds ratio, 0.82; 95% confidence interval, 0.54–1.23; P = 0.369). Among mechanically ventilated patients with shock within the first 24 h of ICU stay, about half had positive fluid responses. Adherence to protocol-based fluid management was associated with improved ICU survival.